Molecular Phylogeny and Taxonomy of the Genus Spumella (Chrysophyceae) Based on Morphological and Molecular Evidence - Jeong, Minseok; Kim, Jong Im; Nam, Seung Won; Shin, Woongghi (Frontiers in Plant Science, 2021)
The genus Spumella, established by Cienkowsky in 1870, is characterized by omnivory, two (rarely three) flagella, a short stick-like structure beneath the flagella, a threadlike stalk, cell division via constriction and cyst formation. Since the first phylogenetic study of Spumella-like flagellates, their paraphyly has consistently been shown, with separation into several genera. More recently, Spumella was carefully investigated using molecular and morphological data to propose seven new species. Classification of this genus and knowledge of its species diversity remain limited because Spumella-like flagellates are extremely difficult to identify based on limited morphological characters. To understand the phylogeny and taxonomy of Spumella, we analyzed molecular and morphological data from 47 strains, including 18 strains isolated from Korean ponds or swamps. Nuclear SSU, ITS and LSU rDNA data were used for maximum likelihood and Bayesian analyses. The molecular data divided the strains into 15 clades, including seven new lineages, each with unique molecular signatures for nuclear SSU rRNA from the E23-2 to E23-5 domains, the spacer between the E23-8 and E23-9 domains of the V4 region and domain 29 of the V5 region. Our results revealed increased species diversity in Spumella. In contrast to the molecular phylogeny results, the taxa showed very similar cell morphologies, suggesting morphological convergence into simple nanoflagellates to enable heterotrophy. Three new species produced stomatocysts in culture. Aspects of stomatocyst morphology, including collar structure, surface ornamentation, and cyst shape, were very useful in differentiating the three species. The general ultrastructure of Spumella bureschii strain Baekdongje012018B8 and S. benthica strain Hwarim032418A5 showed the typical chrysophyte form for the leucoplast, a vestigial chloroplast surrounded by four envelope membranes, supporting the hypothesis that Spumella evolved from a phototroph to a heterotroph via the loss of its photosynthetic ability. Seven new species are proposed: S. benthica, S. communis, S. longicolla, S. oblata, S. rotundata, S. similis, and S. sinechrysos.